Differences Of The Effectiveness Of The Tai Chi Method On Reducing Insomnia And Hypertension In Elderly - Sabirin Berampu; Elsaria Br Sembiring (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Hypertension is caused by stiffness in the arteries which results in an increase in blood pressure which can cause strokes in patients so that they cannot carry out daily activities, it can even be fatal, such as rupture of blood vessels in the brain which can cause death. If an elderly person experiences sleep disorders, it will worsen the underlying disease so that it will have an impact on health. The purpose of this study is the difference in the effectiveness of the Tai Chi method on reducing insomnia and hypertension in the elderly. This type of research is quantitative with a quasi-experimental design. The sample used is the elderly who live in the village of Lau Rakit. The sampling technique used is the Probability Sampling technique. Data were analyzed using Paired T-Test and One Way Anova (<0.05). The results showed that in the insomnia intervention group the p-value was 0.01 and in the hypertension intervention group the p-value was 0.02, which means that the Tai Chi exercise intervention group was effectively used to treat insomnia and hypertension, while in the control group the p-value was 0.16. it means that in the control group there is no effective change. The results of the ANOVA test obtained a p value of 0.04 < 0.05, which means that there is a significant difference between the three groups. It is recommended for the elderly to be able to do Tai Chi exercises regularly to overcome the problems of insomnia and hypertension.